Chlorine-assisted synthesis of Fe3C-filled mm-long vertically aligned arrays of multiwall carbon nanotubes. (24th October 2018) - Odunmbaku, Omololu; Boi, Filippo S; Guo, Jian; Lan, Mu; He, Yi; Yu, Tian; Wang, Shanling; Xiang, Gang
Abstract: Recent reports have shown that chlorine-radicals can be beneficial for the growth of Fe3 C filled carbon nanotubes (CNTs) and the control of their filling-ratio. Here we use such chlorine-assisted approach to demonstrate the controlled synthesis of vertically aligned arrays of mm-long multiwall CNTs filled with large quantities of ferromagnetic Fe3 C. CNTs-lengths up to 2 mm can be achieved through the control of the ferrocene concentration and the thickness of the SiO2 layer of the substrate for a fixed dichlorobenzene concentration.